Suitability of soil and landscape for rapeseed (Brassica napus subsp. napus L.) growing - Jozef Vilček; Stanislav Torma; Štefan Koco; Ján Halas (Scientific Reports)
Abstract The analysis of the suitability of soils for rapeseed (Brassica napus, subsp. napus L.) cultivation in Slovakia showed that there are enough soils suitable for its effective cultivation. Of the total area of agricultural land in Slovakia, 23% is potentially very suitable, 31% is suitable, 14% is less suitable, and 32% is unsuitable soils for rapeseed growing. Spatial analysis of rapeseed areas declared by farmers in the GeoSpatial Aid Application database system showed that 30% of the areas are in land plots with an area of less than 5 ha and 25% of the areas are located in plots with an area between 10 and 25 ha. Rapeseed as subsequent crop was grown after wheat in 68% of cases and after barley in 27% of cases. Rapeseed as fore crop was used for wheat in 71% of cases, for barley in 14% and for maize in 9%. In the period since 2018 to 2023, in fact, rapeseed was actually grown on very suitable (50.1%) and suitable (39.0%) soils for its cultivation. The analysis of the pedological parameters of the soils executed by geographic information systems showed the trend of its dominant cultivation on high-quality soils such as Chernozem (20.5%), Haplic Luvisols (19.4%), Eutric Luvisol (17.8%) and Mollic Fluvisol (10.1%). Rapeseed is no longer grown on slopes above 7 degrees. Areas on a plane up to one degree (43.4%), an undulating plane from 1 to 3 degree (27.7%) and a gentle slope from 3 to 7 degree (25.6%) dominate. Of the grain size categories, loamy soils are the most represented (69.4%), followed by clay-loamy soils (17.9%), and sandy-loamy soils (5.7%). Concerning soil deep and gravely content, deep soils without a gravely (85.7%) absolutely dominate.